2021
DOI: 10.1002/cmdc.202001004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Exploration of Methionine 274 Acting as a “Switch” of the Selective Pocket Involved in HDAC8 Inhibition: An in Silico Study

Abstract: The overexpression of histone deacetylase 8 (HDAC8) causes several diseases, and the selective inhibition of HDAC8 has been touted as a promising therapeutic strategy due to its fewer side effects. However, the mechanism of HDAC8 selective inhibition remains unclear. In this study, flexible docking and in silico mutation were used to explore the structural change of methionine (M274) during HDAC8 binding to inhibitors, along with the reason for this change. Meanwhile, steered and conventional molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This observation contradicted the postulation of a computational study which suggested that leucine instead of methionine is unable to act as a switch that opens a side pocket for the binding of HDAC8-selective L-shaped inhibitors [ 21 ]. We anticipated that the replacement of methionine by the smaller amino acid alanine in HDAC8 M274A would create a constitutively open HDAC8-selective pocket between the L1- and L6-loop, with facilitated access for L-shaped inhibitors.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…This observation contradicted the postulation of a computational study which suggested that leucine instead of methionine is unable to act as a switch that opens a side pocket for the binding of HDAC8-selective L-shaped inhibitors [ 21 ]. We anticipated that the replacement of methionine by the smaller amino acid alanine in HDAC8 M274A would create a constitutively open HDAC8-selective pocket between the L1- and L6-loop, with facilitated access for L-shaped inhibitors.…”
Section: Resultsmentioning
confidence: 81%
“…By analyzing crystal structures of L-shaped inhibitors bound to smHDAC8 from Schistosoma mansoni , a special selective binding pocket was observed between the catalytic tyrosine and the L1–L6 loop [ 20 ]. A computational study suggested that this selective binding pocket is a transient binding pocket, which opens upon binding of L-shaped inhibitors, and is controlled by movement of M274 [ 21 ]. Moreover, this structural change was not observed when M274 was replaced by leucine in the same computational study, leading to the hypothesis that M274 is the key factor responsible for selective HDAC8 inhibition [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations